Comparison of apical root resorption at different times and malocclusions - Poletto, Raquel Silva (2020)
Introduction: External apical root resorption is a well-known consequence of orthodontic treatment. The objective of this study was to compare the apical root resorption in patients with Class I and Class II malocclusion treated with 0.021x0.025 inch archwire in anterior retraction with those who were treated with 0.019x0.025 or 0.018x0.025 inch archwire in anterior retraction and additionally to compare this patients emphasizing the initial malocclusion. Methods: A sample of 110 patients treated with four premolar extractions was divided into four groups, combined two by two. At first comparison the sample was divided in two groups: Group 1 (G1) consisted of 46 patients who were treated with 0.021x0.025 inch archwire in anterior retraction after four premolar extraction. Group 2 (G2) consisted of 46 patients who were treated with 0.019x0.025 or 0.018x0.025 inch archwire in anterior retraction after four premolar extraction. At second comparison the sample was also divided into two groups: Group 1 (G1) consisted of 57 patients with Class I malocclusion treated with rectangular archwire in anterior retraction after four premolar extraction. Group 2 (G2) consisted of 53 patients with Class II malocclusion treated with rectangular archwire in anterior retraction after four premolar extraction. All groups were matched regarding initial age, treatment time, sex distribution. Pre- and posttreatment lateral cephalometric and periapical radiographs were evaluated. Mann Whitney and t tests were performed to compare the initial status, the treatment changes and the quantity of resorption of the groups. Results: There was a greater extrusion of maxillary incisors in group 1 and the apical root resorption was greater in group 1 both in maxillary and mandibular incisors at first comparison. there were no difference in root resorption degree after orthodontic treatment between the groups at second comparison. Conclusion: Greater stainless steel rectangular archwire thickness produces more root resorption than thinner rectangular archwires. Class I and Class II malocclusions treated with 4- premolar extractions present similar degrees of root resorption. Therefore, correction of the sagittal discrepancy is not associated with a greater degree of resorption.